Unraveling Islamic Fundamentalism and Radicalism: A Literature Review Perspective - Maraulang, Maraulang (Journal of Indonesian Islamic Studies, 2024)
This study aims to provide a comprehensive review of the literature on Islamic fundamentalism and radicalism to enhance our understanding of these phenomena and their implications. By examining various sources, including academic articles, policy reports, and historical records, this research seeks to uncover the multiple dimensions of fundamentalism and radicalism. The study will explore the socio-political, economic, and cultural factors contributing to the emergence and spread of these ideologies. Additionally, the research will analyze the effectiveness of various counter-radicalization strategies implemented by governments and international organizations. The study employs a literature review methodology to systematically analyze existing research on Islamic fundamentalism and radicalism. This approach was chosen for its ability to consolidate and synthesize various scholarly sources, providing a comprehensive overview of the current state of knowledge on the topic. By reviewing and comparing different studies, this approach aims to reveal patterns, identify key themes, and highlight areas where further research is needed. The selected sources include peer-reviewed journal articles, books, and scholarly essays that are relevant to the topic, methodologically rigorous, and authored by credible scholars. The research findings indicate that historical perspectives on Islamic fundamentalism reveal that this phenomenon is rooted in various historical and ideological developments, particularly in response to colonialism, political instability, and socio-economic changes. Contemporary manifestations of Islamic radicalism are highly diverse, reflecting the different contexts in which they arise, including geopolitical conflicts and domestic discontent. Comparative analysis with other fundamentalisms, such as Christian and Hindu fundamentalism, shows similar patterns in resistance to modern and secular influences. The socio-political impact of Islamic fundamentalism includes changes in domestic policies, diplomatic challenges, and social cohesion. The study also highlights scholarly debates on the interpretation of religious texts, external influences, and socio-political factors driving radicalization.